A vaca vai para o brejo: urbanidade e juventude através da revista Chiclete com Banana (1985-1990) - Cezaretto, André Luís Sanchez (2010)
This essay had the objective of analysing the urban daily life in São Paulo during 1985 and 1990, by using the comic Chiclete com Banana , by Angeli. The rich cartoonist s point of view about several themes from the mentioned period was the reason to choose this cartoon as the source of this research. Therefore, it was organized as follows: At The Introduction there was a consideration about the usage of stories as primary source for research to the historian, then comes the following three chapters. 1- At the first one there was a general approach to the cartoon, observing its essencial aspects besides HQs themselves and searching the common themes, the beginning point was to understand Angeli s view of the world in order to comprehend where his humor came from; 2- The second chapter was exclusively dedicated to Angeli s view of São Paulo city, noticing that his representations of the capital significatively interfered at his own characters characterization which was essential to the story development; 3- At last, the third chapter was dedicated to Angeli s perception of the youths from that period, checking that the author distinguished them in two basic groups, the first from a middle class, the little bourgeois with empty manifestations in terms of contents and also conservative ones, and the second emergent group, the lower class appeared with defiant and original contents and communicated with Angeli through the letters section. Finally, an approach to the characters such as Meiaoito, Wood&Stock e Rê Bordosa presented a rich comparison among youth manifestations from the sixties and the eighties